2008
DOI: 10.1007/s11706-008-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of H-oleoyl-carboxymethyl-chitosan and the function as a coagulation agent for residual oil in aqueous system

Abstract: In this study, H-form oleoyl-carboxymethylchitosan (H-O-CMCS) was prepared as a coagulation agent to clean up the residual oil from the waste-water of oil extraction (WWOE). The Fourier transform infrared (FTIR) spectra confirmed the formation of an amide linkage between amino groups of carboxymethyl chitosan (CMCS) and carboxyl groups of oleic acid. The adsorption capacities of four absorbents (H-O-CMCS, chitosan, activated carbon and polyaluminium chloride (PAC)) for the residual oil were investigated. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In conclusion, rotenone-loaded DACMCs shows the best release profiles where it took more than 51 hours to release the rotenone loaded. The increase of DACMCs ratios provide a bigger space for the hydrophobic interaction between rotenone and the hydrophobic group in DACMCs to occur [8]. As reported by Li et al [9], the burst release provides an effective concentration of rotenone to be attained.…”
Section: In Vitro Release Studies Of Rotenone-loaded Amphiphilic Chitmentioning
confidence: 75%
See 2 more Smart Citations
“…In conclusion, rotenone-loaded DACMCs shows the best release profiles where it took more than 51 hours to release the rotenone loaded. The increase of DACMCs ratios provide a bigger space for the hydrophobic interaction between rotenone and the hydrophobic group in DACMCs to occur [8]. As reported by Li et al [9], the burst release provides an effective concentration of rotenone to be attained.…”
Section: In Vitro Release Studies Of Rotenone-loaded Amphiphilic Chitmentioning
confidence: 75%
“…Furthermore, the peaks represent -NH2 group at 1636 and 1628 cm -1 are shifted and decrease in each OCMCs, DCMCs and DACMCs as compared to chitosan. This can be related to reaction between the amino groups with the alkyl groups from each amphiphilic chitosan derivatives [8]. Besides that, absorption bands for OCMCs and DACMCs at 1069 and 1073 cm −1 significantly decreased after alkylation reaction, indicating that substitution reaction occurred on amide linkage [13].…”
Section: Ftir Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…Since in our previous fundamental studies we found that oxygen atoms of κC backbone can form coordinated bonds with cations (i.e., the counterions of the I -/I 3 -redox mediator: Na + ) [32], in this work we expected that the introduction of oxygen-containing substituent groups in the κC chain would have provided more sites for cations to coordinate, thus increasing the ionic conductivity with respect to the raw material. Accordingly to Sun's reaction [33], we converted κC into carboxymethyl-κ-carrageenan (CκC): the process consisted of the deprotonation of the hydroxyl groups of κC by a strong base (NaOH), followed by the reaction between κ-carrageenan alkoxides and monochloroacetic acid. Characterizations useful to demonstrate the successful completion of the process, namely elemental analysis (Table A1), 13 C NMR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CM-chitosan was prepared from chitosan [22,23]. 10 g chitosan samples with different MWs (MW 160 kDa, MW 5.2 kDa) were respectively added in 20 mL alkali solution (60%; w/w) to be swelled and alkalized at 50°C for 4 h. The temperature was maintained in a water bath (thermocontroller, Comabiotech.…”
Section: Preparation Of Cm-chitosan With Different Mwsmentioning
confidence: 99%